Сенсор для контроля процессов формирования и набора прочности вяжущих сред - Zaichenko, L. M.; Serediuk, A. I.; Fotiy, V. D.; Shevchuk, Yu. F. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Studies were carried out on the strain and pressure sensitivity of layered low-dimensional А3В6-type single crystals. The baric sensitivity coefficient for indium selenide (InSe) single crystals is 10−8−10−7 Pa−1, and the strain sensitivity is 103−104. The possibility of using such sensors for non-destructive monitoring of setting, strength development, and solvent crystallization processes in binding media is demonstrated, including for monitoring the condition of products cast in various compounds.